Pemberdayaan Ekonomi Kreatif Masyarakat Desa Teluk Sungka Melalui Pemanfaatan Limbah Sabut Kelapa dan Lateks menjadi Produk Kerajinan Bernilai Jual - Ernidawati, Ernidawati; Irianti, Mitri; Ma'aruf, Zuhdi; Zulhelmi, Zulhelmi; Zulkarnain, Zulkarnain; Susanti, Hevi; Hayati, Isnaria Rizki; Ulfa, Zulia; Jannah, Miftahul; Andrina, Hanifaturrahmi; Idris, Idris; Sinaga, Ego Srivajawaty (Unri Conference Series: Community Engagement, 2025)
This community service activity was carried out in Teluk Sungka Village, Gaung Anak Serka District, Indragiri Hilir Regency, with the aim of empowering the community through the utilization of coconut coir waste into innovative handicraft products with market value. Until now, coconut coir has only been regarded as waste and has not been optimally utilized, even though it has considerable economic potential. The method used in this activity was a participatory approach, actively involving the community through several stages, namely identifying potential, collecting materials, conducting training, practicing handicraft production, and providing assistance during the production process. The coconut coir was processed into handicrafts with the help of latex as an adhesive to produce products such as flower pots and various other decorative items. The results of the activity showed that the community was able to process coconut coir into more useful products that have economic value and the potential to become an additional source of income. Through this program, the community gained new skills while also opening opportunities for the development of creative economies based on local potential.